Observation of a case of pneumatosis small intestine cystic - Mariño, Ana; Müller, Augusto; Morales, A.; Iraola, María Luisa (Cirugía del Uruguay, 1991)
The authors present a case of cystic pneumatosis of the sma/1 intestine, resected in the course of /aparotomy due to perforated peptic ulcus. They analyse this /esion·s morphology from the anatomopathologica/ point of view, confirming once again the lesiona/ sequency they previous/y described regarding a case with identical topography in 1986. They discuss treatment and point out surgical abstention in uncomplicated cases and adequate treatment of the pathological condition that seems to generate the production of these lesions.